Complex species status for extinct moa (Aves: Dinornithiformes) from the genus Euryapteryx. - Leon Huynen; David M Lambert (PLoS ONE)
The exact species status of New Zealand's extinct moa remains unknown. In particular, moa belonging to the genus Euryapteryx have been difficult to classify. We use the DNA barcoding sequence on a range of Euryapteryx samples in an attempt to resolve the species status for this genus. We obtained mitochondrial control region and the barcoding region from Cytochrome Oxidase Subunit I (COI) from a number of new moa samples and use available sequences from previous moa phylogenies and eggshell data to try and clarify the species status of Euryapteryx. Using the COI barcoding region we show that species status in Euryapteryx is complex with no clear separation between various individuals. Eggshell, soil, and bone data suggests that a Euryapteryx subspecies likely exists on New Zealand's North Island and can be characterized by a single mitochondrial control region SNP. COI divergences between Euryapteryx individuals from the south of New Zealand's South Island and those from the Far North of the North Island exceed 1.6% and are likely to represent separate species. Individuals from other areas of New Zealand were unable to be clearly separated based on COI differences possibly as a result of repeated hybridisation events. Despite the accuracy of the COI barcoding region to determine species status in birds, including that for the other moa genera, for moa from the genus Euryapteryx, COI barcoding fails to provide a clear result, possibly as a consequence of repeated hybridisation events between these moa. A single control region SNP was identified however that segregates with the two general morphological variants determined for Euryapteryx; a smaller subspecies restricted to the North Island of New Zealand, and a larger subspecies, found on both New Zealand's North and South Island.